Investigation of electrical responses of a proton exchange membrane (PEM) fuel cell - Cai, Ruitang (2009)
In this project, the Nexa Power Module was treated to different load demands and the transient response was analyzed in detail; in order to verify if it is suitable for use as a backup power source. The first step taken in this project was to read up on the working principals of the PEMFC and other related journals and articles. Next, the Nexa Power Module’s User Manual was studied in order to find out how to operate the Nexa Power Module correctly. Then, experiments were conducted to measure the various operating parameters of the Nexa Power Module in different load-demand conditions. The recorded values were investigated in detail to give a thorough description on the Nexa Power Module’s limitations as a backup power source.